Phaco-nucleotomy techniques in management of pseudoexfoliation syndrome - Bansal, Amol; Malik, K. P.S.; Malik, V. K.; Jain, Kirti (Nepalese Journal of Ophthalmology, 2017)
Introduction: Pseudoexfoliation syndrome is a common clinically important systemic condition characterized by the pathological production and accumulation of an abnormal fibrillar extracellular material in many intraocular and extra ocular tissues. Many studies have shown that pseudoexfoliation syndrome patients have higher rates of intraoperative complications during cataract surgery compared to the patients without it. Objectives: To compare Phaco-chop and Divide and Conquer techniques of phacoemulsification, in the management of pseudoexfoliation syndrome in terms of intraoperative complications. Materials and methods: It is a hospital based prospective study of 90 patients with cataract and pseudoexfoliation syndrome attending ophthalmology outpatient department in our hospital. Results: The mean age of patients in the study was 61.7 years with equal number of unilateral and bilateral cases. Intra operative complications noted in vertical chopping technique was only pupil constriction in 6.7%, no other complications were seen in this technique, whereas in horizontal chopping, 13.3% had pupil constriction, 6.7% had difficulty in chopping, 3.3% had zonular dehiscence and 3.3% had posterior capsular rent . In divide and conquer technique 16.7% had pupil constriction, 10% had difficulty in trenching, 3.3% had posterior capsular rent. Almost all the patients (97.8%) were implanted with intraocular lens after employment of various surgical modifications. Conclusion: Vertical chopping techniques scores over horizontal chopping and divide and conquer technique of phacoemulsification with good surgical outcome because of less complications.